Myocardial infarction in young patients. Is everything so obvious? - M. V. Zykov; O. L. Barbarash (Евразийский Кардиологический Журнал)
The review is devoted to the analysis of literature data on the features of the course, diagnosis and treatment of myocardial infarction at a young age. Despite the relevance of the problem of myocardial infarction in young people, there is no specific approach to the management and examination of such patients in current clinical guidelines. Literature search was carried out in the following databases: PubMed, Google Scholar, Web of Science from 1990 to 2023 for all studies with the keywords “myocardial infarction and young age”, “atherosclerosis and young age”, “atherothrombosis and young age”. An analysis of all available clinical recommendations of leading specialized societies in the field of cardiology, hematology, and angiology was also carried out. The presented review is not systematic view of the specifics of the subject, its breadth, as well as the task set – to expand the clinical thinking of the doctor. It is undeniable that primary prevention of myocardial infarction is more effective. Given the annual increase in the number of myocardial infarctions at a young age, it is necessary to create a special tool for risk stratification in young patients, since there is no such tool in the clinical guidelines. Despite the greater contribution of non-atherogenic causes to the development of myocardial infarction in young patients, atherosclerosis is still the main cause of its development. The authors of the review confirm the fact that there is currently no specially developed algorithm for managing patients with myocardial infarction at a young age, based on the identification of a number of traditional and non-traditional risk factors, on enhanced rehabilitation measures. All these positions are currently formulated in the aims and objectives of a special sevenyear study of myocardial infarction in young patients planned at our institute.